Kajian Geograﬁ Politik Pada Peristiwa Penaklukkan Khaibar di Masa Pemerintahan Nabi Muhammad SAW - Kaslam, Kaslam (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
The conquest of Khaibar in Islamic history is one of the important events that has an interesting political geography dimension to study. This incident occurred in 628 AD, when Muslims experienced conflict with Jewish tribes in Khaibar, which marked strategic steps in securing and strengthening the position of Muslims in the region. The purpose of this article is to analyze the conquest of Khaibar during the reign of Prophet Muhammad SAW using a political geography approach. By using the library research method, we collect reference materials from credible sources. The result is the Prophet Muhammad SAW. used the strategy of Urban Warfare in the conquest of Khaibar's strongholds. Apart from that, Jungle Warfare was also implemented by controlling air and logistical sources outside the fort. Because it is very dependent on the defense of the fort, the tactic used is to control one fort together. And the final strategy is to form small teams to outwit and break up the concentration of the Jewish army, so that all the strongholds are conquered by the Muslims.